Clinical Characteristics and Mortality of a Hospitalized 13 Years Old Patient with Covid-19: A Case Report - Chavoshi, Tahereh; Mahdavi, Alireza; Rouzrokh, Mohsen; Shafa, Amir; Tabatabaei, Sedigheh Rafiei; Fahimzad, Seyed Alireza; Dabbagh, Ali; Marbout, Azar (Iranian Journal of Pediatric Surgery, 2021)
The corona virus is a global problem that threatens human life. According to the latest data from different countries the mortality of this virus in children is less than adult. A 13-year-old girl was hospitalized for 6 months following a gunshot trauma and its complications. When her general condition was finally improving, she was diagnosed with the corona virus and passed away. Children who are suffering from underlying diseases and need medical care are at a higher risk of death from the corona virus.